Aetiology and diagnostics of Long Face Syndrome – based on literature - Sobieska, Ewa; Fester, Aneta; Ciok, Edyta; Zadurska, Małgorzata (Journal of Stomatology, 2015)
A hyperdivergent facial type, adenoid face, long face syndrome (LFS), high-angle patient type – these terms describe patients with increased inclination of the mandibular body base (ML) relative to the anterior cranial base (NSL). According to Riedel, when the value of this angle (ML/NSL) exceeds 38°, the patient can be classified as a high-angle type. The paper aims at presenting a review of available literature on LFS and raising awareness among clinicians that the long face syndrome is a group of typical characteristics associated with the structure of the facial skeleton and that one parameter of a cephalometric analysis is not sufficient for its diagnosis. The diagnostics of LFS is based on extra- and intraoral examination and a cephalometric analysis with consideration of aetiological factors.